The Immunosuppressant Effect Comparation Between Ethyl Acetate and n-Butanol Fractions of Kalanchoe Pinnata (Lmk) Pers In 2,6,10,14 Tetramethylpentadecane-Treated Mice - Niken Indriyanti; Joewono Soeroso; Junaidi Khotib (Journal of Tropical Pharmacy and Chemistry, 2017)
Immunosuppressant drugs are the main treatment of lupus patient. The ACR and SLICC treatment guidelines are able to increase the quality of life, but the outcome is not satisfying since the off-label therapy of corticosteroids and cytotoxic drugs give a lot of side effects. Many breakthrough efforts still develop in order to find the safe and effective drugs for lupus, such as finding immunosuppressant drugs from natural resources. One of the potential resources is Kalanchoe pinnata (Lmk) Pers, which have immunosuppressant, anti-inflammatory, antinociceptive, and antioxidant effects. Thus, in the previous study, we found the effect of the aqueous extract of Kalanchoe pinnata (Lmk) Pers is active to repair the lupus manifestation in 2,6,10,14 tetramethylpentadecane (TMPD)-treated mice. Then, this research was focused on the in vivo immunosuppressant effect of a flavonoid-rich fraction of the extract which was consisted of the ethyl acetate (FE) and n-butanol (FB) fractions. The induction method and the extraction procedure were the same as the previous study and then the fractionation was performed by using liquid-liquid extraction. After 2-week treatment of both fractions, we obtained the differences in the total leukocytes, organ indexes, and also the spleen, kidney, and joint structure parameters. The total leukocyte of the FE group was 3,600Â±264 cells/mm3, which was lower than that in the FB group. The spleen and kidney indexes increased after the administration of FB fraction, while the FE fraction was not. At last, despite the histology observation of spleen resembled mild structural changes differences, the clear differences between both treatment groups occurred in the kidney and joint histology. The differences led to a conclusion that the FE fraction has the better immunosuppressant effect in TMPD-treated mice.